Desmoplastic fibroma of the femur with atypical image findings: A case report - Xu, Yongming (Medicine (Baltimore), 2018)
RATIONALE: Desmoplastic fibroma of the bone (DFB) is an extremely rare benign bone tumor, which can occur in any bone at all ages. Herein, we report a case of non-specific imaging findings. PATIENT CONCERNS: A 25-year-old female patient was consulted in the Armed Police General Hospital (Beijing, China) due to repeated pain in the right thigh lasting over 1 year. Imaging examination revealed a space-occupying lesion in the right femur. DIAGNOSIS: Desmoplastic fibroma of the femur INTERVENTIONS: Wide surgical resection OUTCOMES: At the 1-year follow-up visit, no relapse in the tumor was observed. LESSONS: In this case report, we described and emphasized the particularity of the case examined and the possible non-specificity of the imaging results of some DFB cases.